Produção de textos em contextos de cursos preparatórios para o ENEM: a questão da autoria - Carvalho, Kesley Alves de (2020)
First instituted in 1998 to evaluate high-school senior students in several areas of knowledge, Enem – Exame Nacional do Ensino Médio, throughout the years and after a few changes, has been considered the greatest and most important exam for admission in Brazilian higher education institutions. Since its institution, one of the most concerning sections of Enem for most candidates is the argumentative essay they must write from a topic proposal. Considering the preparation for this exam, this work aims at analyzing essays written by students from a preparatory course located in a city from Southern Minas Gerais, and, by adopting an indicator paradigm, this work also investigates how authorship is constituted and built by student-candidates in preparatory schools. To begin with, we approach the history of essay writing in Brazil to, after reaching the age of text production under a social-interactionist perspective, discuss how writing is taught in Eem preparatory courses. Afterwards, we assess the resources and argumentative strategies found in student-written essays, from which we analyze authorship. The analyses are based on research studies carried out by interactionist and social-interactionist authors, such as Pécora (2011), Geraldi (1997; 2004), and Possenti (2002), who, additionally, forms the grounds for investigating authorship in this study. This work also leads to a reflection on how essay production is approached in contexts related to exams for admission in higher education institutions. Lastly, results show the need to provide student-candidates with conditions to become proper authors and own their statements.